Political Instability in Pakistan: Causes, Implications and A Way Forward - Shagufta Zulfiqar; Ufia Tahir (ASIAN Journal of International Peace & Security (AJIPS), 2025)
Political instability has emerged as a defining challenge for Pakistan, significantly undermining governance, public trust and developmental progress across the country since 2022. This study examines this period of turmoil, characterized by fragile democratic institutions and the enduring influence of military in political affairs. Employing a qualitative research methodology based on secondary sources, including scholarly articles, reports, newspapers and official documents, the study identifies both domestic and external drivers of political instability. Internally, systemic corruption, bureaucratic inefficiency and regional tensions, have eroded institutional legitimacy, weakened service delivery, and diminished public confidence in the political system. Externally, Pakistan’s reliance on foreign aid, international alliances and military support has influenced policy priorities, creating structural dependencies that compromise autonomous decision-making. This study applies Interdependence Theory to analyze how these interconnected factors collectively shape political outcomes and governance effectiveness. The findings reveal that political instability has generated cycles of inefficiency, mistrust and public dissatisfaction, impeding long-term development, policy continuity and institutional strengthening.